2022
DOI: 10.3390/ijms232314675
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Cosmetic and Dermatological Properties and Safety of Use of Model Skin Tonics with Kombucha-Fermented Red Berry Extracts

Abstract: Kombucha is a health-promoting beverage that is produced by fermenting sweetened tea using symbiotic cultures of bacteria belonging to the genus Acetobacter, Gluconobacter, and yeast of the genus Saccharomyces. This study compared the cosmetic and dermatological properties of the extracts of the following redberries: R. rubrum, F. vesca, and R. idaeus, and their ferments, which were obtained by fermentation for 10 and 20 days using tea fungus. For this purpose, the fermented and non-fermented extracts were com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 61 publications
(60 reference statements)
3
5
0
Order By: Relevance
“…Similar correlations were observed by Ziemlewska et al [35]. The smallest deviations from the physiological pH of the skin were found for tonics with added extracts, while the largest differences were shown by formulations with ferment, due to the acidic environment of the ferment itself.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…Similar correlations were observed by Ziemlewska et al [35]. The smallest deviations from the physiological pH of the skin were found for tonics with added extracts, while the largest differences were shown by formulations with ferment, due to the acidic environment of the ferment itself.…”
Section: Resultssupporting
confidence: 87%
“…There were also no relevant changes in TEWL level considering fermentation time (10 and 20 days). Ziemlewska et al evaluated the TEWL and skin hydration of model skin tonics with red berry extracts and its Kombucha ferments [35]. Similar to our study, they found that formulations containing the extract or ferment showed a more favourable moisturizing effect compared to the base tonic, but formulations containing kombucha ferments, R. ruburum and R.idaeus, after 10 days had less beneficial effect on skin hydration compared to tonics with plant extracts.…”
Section: L*supporting
confidence: 86%
See 1 more Smart Citation
“…Although this solvent is not very effective for isolating various phenolic compounds, the water extract is safe for cells and microorganisms and can be subjected to fermentation. Kombucha, which is the mixture of a symbiotic culture of bacteria from the Acetobacter and Gluconobacter genera and yeast belonging to Saccharomyces, was used to trigger the fermentation because our previous works have shown its effectiveness in inducing beneficial changes in plant material [ 26 , 27 , 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, there has been growing interest in using as many raw materials of natural origin as possible in cosmetic products. New technologies for the use of plant raw materials are increasingly being sought, so that they are characterized by the greatest possible amount of biologically active compounds [ 1 ]. There is also growing interest in the use of plant ferments in cosmetic preparations.…”
Section: Introductionmentioning
confidence: 99%